2019
DOI: 10.1080/22797254.2019.1617642
|View full text |Cite
|
Sign up to set email alerts
|

The continuous built-up area extracted from ISS night-time lights to compare the amount of urban green areas across European cities

Abstract: The presence of urban green areas significantly impacts urban inhabitants' well-being. However, comparative studies across European cities are constraint by urban administrative boundaries, which commonly do not match the continuous built-up urban area. This makes comparative research on environmental indicators very problematic, as administrative boundaries are not usually appropriate to define the urban human environment. Therefore, this study aimis to explore the use of night-time light (NTL) images of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Through the comparison, it was found that the two main centers in the plan were consistent with the experimental results in this paper: Yan'an Road and the area near West Lake on the north side of 5 Liangzhu Group Center…”
Section: Comparison Of Main Centers and Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Through the comparison, it was found that the two main centers in the plan were consistent with the experimental results in this paper: Yan'an Road and the area near West Lake on the north side of 5 Liangzhu Group Center…”
Section: Comparison Of Main Centers and Analysissupporting
confidence: 86%
“…However, to some extent, traditional methods relying on socio-economic and statistical data may have the following problems:Access to spatial disaggregated data. • Insufficient background and prior knowledge of the research area.Compared with traditional methods, remote sensing data, especially nighttime light remote sensing data, have been widely used in urban studies [3] because of their free availability, global coverage, and high temporal resolution [4,5]. Sensors on a satellite can capture the brightness of cities, farms, industrial areas, fishing vessel lights, forest fires, and other human activity areas at night and form a nighttime light image [6,7].…”
mentioning
confidence: 99%
“…Based on a collaboration between the Complutense University of Madrid, NASA, and ESA, the calibrated ISS images became available through paid service at NOKTOsat (https://www.noktosat.com/). Currently, the ISS images have been used for studies on identification of urban and internal lighting types [54][55][56][57], light pollution [58,59], and socioeconomic activities [60][61][62].…”
Section: Other Satellites and Cubesatsmentioning
confidence: 99%
“…The assessment of air quality can be specifically assessed with new constellation of satellite systems (see, for example, the recent ESA Sentinel5 mission) as required for quantifying indicator 11.6.2 or for monitoring waste management for indicator 11.6.1. In such a framework, EO can also be used for monitoring green spaces in urban areas as specifically requested in target 11.7 (Wicht & Kuffer, 2019).…”
Section: Editorialmentioning
confidence: 99%